Влияние применения криоконсервированной суспензии клеток плаценты на показатели периферической крови и костного мозга животных с адъювантным артритом - Луценко, Е.Д.; Останков, М.В.; Бондарович, Н.А.; Гольцев, А.Н. (Problems of Cryobiology and Cryomedicine, 29(1), 28–43., 2019)
На модели адъювантного артрита у мышей линии СВА/Н исследованы гематологические показатели, определен уровень циркулирующих иммунных комплексов (ЦИК) и количество стволовых кроветворных клеток (CD34 + CD38 – , CD117 + ) в костном мозге (КМ) до и после применения нативной и криоконсервированной в различных режимах суспензии клеток плаценты (СКП). СКП криоконсервировали с 10% диметилсульфоксида или 10% пропандиосахароля. Максимальное терапевтическое действие оказывало введение нативной СКП (14-е сутки) и суспензии, криоконсервированной с пропандиосахаролем (28-е сутки). Введение любой из суспензий корригировало скорость оседания эритроцитов, ЦИК, количество ядросодержащих клеток в КМ, но эффект проявлялся в различные сроки. Применение криоконсервированных суспензий способствовало восстановлению индекса пролиферативной активности стволовых кроветворных клеток. В зависимости от условий криоконсервирования СКП изменялись свойства вводимой суспензии, что влияло на сроки восстановления количества CD117 + -клеток. __________________________________________________________________________________________ На моделі ад’ювантного артриту у мишей лінії СВА/Н досліджено гематологічні показники, визначено рівень циркулюючих імунних комплексів (ЦІК) та кількість стовбурових кровотворних клітин (CD34 + CD38 – , CD117 + ) у кістковому мозку (КМ) до і після застосування нативної та кріоконсервованої за різними режимами суспензії клітин плаценти (СКП). СКП кріоконсервували з 10% диметилсульфоксида або 10% пропандіосахаролю. Максимальна терапевтична дія спостерігалась після введення нативної СКП (14-а доба) і суспензії, кріоконсервованої з пропандіосахаролю (28-а доба). Введення будь-якої суспензії коригувало швидкість осідання еритроцитів, ЦІК, кількість ядровмісних клітин у КМ, але ефект проявлявся в різні терміни. Застосування кріоконсервованих суспензій сприяло віднов ленню індексу проліферативної активності стовбурових кровотворних клітин. Залежно від умов кріоконсервування СКП змінювалися властивості введеної суспензії, що впливало на термін відновлення кількості CD117 + -клітин. __________________________________________________________________________________________ In the model of adjuvant-induced arthritis in CBA/H mice there were investigated the gematological indices, circulating immune complexes (CIC) in peripheral blood, a number of hematopoietic stem cells: CD34 + CD38 – and CD117 + in bone marrow (BM) before and after applying either fresh or cryopreserved with various regimens placental cell suspension (PCS). PCS was cryopreserved with either 10% dimethyl sulfoxide or 10% propane diol saccharol. The maximum therapeutic effect was found after the introduction of fresh PCS (day 14) and suspension, cryopreserved with propane diol saccharol (day 28). The introduction of any of PCS positively affected the erythrocyte sedimentation rate (ESR), CIC, nucleated cells in bone marrow, but the effect was manifested at different terms. The application of cryopreserved suspensions contributed to the restoration of proliferative activity of hematopoietic stem cells. Depending on the cryopreservation regimen of the PCS, the properties of the injected suspension changed which aﬀ ected the recovery time of the number of CD117 + -cells.
Inﬂuence of Application of Cryopreserved Placental Cell Suspension on Indices of Peripheral Blood and Bone Marrow of Animals with Adjuvant Arthritis
Lutsenko, E. D., Ostankov, M. V., Bondarovich, N. A., & Goltsev, A. N. (2019). Influence of Application of Cryopreserved Placental Cell Suspension on Indices of Peripheral Blood and Bone Marrow of Animals With Adjuvant Arthritis. Problems of Cryobiology and Cryomedicine, 29(1), 28–43. https://doi.org/10.15407/cryo29.01.028
Keywords: артрит; криоконсервирование; плацента; стволовые кроветворные клетки; артрит; кріоконсервування; плацента; стовбурові кровотворні клітини; arthritis; cryopreservation; placenta; hematopoietic stem cells